Comparison of Heat Transfer Measurement Techniques on a Transonic Turbine Blade Tip - O'Dowd, DO; Zhang, Q; He, L; Ligrani, P; Friedrichs, S (2011)
The present study considers spatially resolved surface heat transfer coefficients and adiabatic wall temperatures on a turbine blade tip in a linear cascade under transonic conditions. Five different measurement and processing techniques using infrared thermography are considered and compared. Three transient methods use the same experimental setup, using a heater mesh to provide a near-instantaneous step-change in mainstream temperature, employing an infrared camera to measure surface temperature. These three methods use the same data but different processing techniques to determine the heat transfer coefficients and adiabatic wall temperatures. Two of these methods use different processing techniques to reconstruct heat flux from the temperature time trace measured. A plot of the heat flux versus temperature is used to determine the heat transfer coefficients and adiabatic wall temperatures. The third uses the classical solution to the 1D nonsteady Fourier equation to determine heat transfer coefficients and adiabatic wall temperatures. The fourth method uses regression analysis to calculate detailed heat transfer coefficients for a quasi-steady-state condition using a thin-foil heater on the tip surface. Finally, the fifth method uses the infrared camera to measure the adiabatic wall temperature surface distribution of a blade tip after a quasi-steady-state condition is present. Overall, the present study shows that the infrared thermography technique with heat flux reconstruction using the impulse method is the most accurate, computationally efficient, and reliable method to obtain detailed, spatially resolved heat transfer coefficients and adiabatic wall temperatures on a transonic turbine blade tip in a linear cascade. © 2011 American Society of Mechanical Engineers.